The Effect of Venture Capital on Enterprise Benefit According to the Heterogeneity of Human Capital of Entrepreneur - Jin, Xin; Zheng, Puyang; Zhong, Ziqi; Cao, Yali (Frontiers in Psychology, 2020)
This research aims to explore the role of venture capital (VC) based on the heterogeneity of human capital in the process of transforming innovation capabilities of enterprise into enterprise benefits, and to provide a reference for further research on enterprise performance development. In this study, 483 listed companies that obtained VC before 2018 from China VC database and Wind China financial database are selected as research objects, and relevant data of patent number, return on equity, Tobin’s Q ratio and research and development (R & D) investment ratio of each enterprise are obtained. Enterprise innovation ability is introduced to construct the relationship model of human capital VC, enterprise innovation ability, and enterprise benefit, and the relationship between human capital VC, enterprise innovation ability, and enterprise benefit is analyzed by the multiple regression model. The results show that the number of patents of invested enterprises has an extremely significant positive correlation with the human capital index (P<0.001), and a significant positive correlation with the education level of personnel, the proportion of engineering professionals, and the shareholding ratio of investors (P<0.05). The return on equity and Tobin's Q ratio of enterprises have extremely significant positive correlations with the number of patents of invested enterprises (P<0.001), and have a significant positive correlation with the number of patents of the invested enterprises, the number of patents of the invested enterprises × human capital index, the number of patents of the invested enterprises × education level of the personnel, and the number of patents of the invested enterprises × proportion of engineering professionals (P<0.05). Therefore, the personnel education level and the proportion of personnel with engineering background in the human capital of entrepreneur VC all play a strong value-added role in the transformation of enterprise innovation ability into enterprise benefit. The growth of enterprise benefit depends partly on the level of VC of human capital of entrepreneur.